Conformance Control for Tight Oil Cyclic Gas Injection Using Foam. (11th March 2022) - Wei, Falin; Zhang, Song; Xi, Yilin; Zhu, Zhouyuan; Xiong, Chunming; Zang, Chuanzhen; Li, Junjian
Abstract : Cyclic gas injection has been proven to be an effective enhanced oil recovery (EOR) technique for tight oil reservoirs. During such processes, we expect recovery mechanisms such as oil swelling, oil viscosity reduction, vaporization, and pressure support, which highly relies on the successful conformance control of the injected gas. In this work, we present the numerical simulation study of using foam for improving the conformance control of cyclic gas injection in tight oil reservoir. We focus on improving two categories of conformance control problems using foam, making the injection profile for single well more evenly distributed and mitigating the gas breakthrough to adjacent wells through the connected hydraulic fractures in a multiwell setting. The simulation results show that foam has shown major impact in improving the gas conformance control in both cases. Typical recovery factor improvements are estimated to be up to 1% for lean gas injection in this tight oil reservoir. In conclusion, we have demonstrated the great potential of using foam to improve the conformance in tight oil cyclic gas injection process.